Selected cases in the conduct of Kenyan foreign policy sine 1992 - Wanyama, Leonard (My University, 2012)
Since the end of the cold war, Kenya’s foreign policy has become inextricably linked to its domestic conditions. This study examines this correlation by examining three cases, namely: Kenya’s role and place in the East African Community (EAC); and its relations with its neighbours-Sudan in the north and Somalia in the north east. A key assertion is that Kenya’s foremost foreign policy objective is the pursuit of a national interest whose central features include national security, political stability, and economic development. This report illustrates the influence of multiparty politics on Kenya’s foreign policy formulation, highlighting some of the continuities form the pre-cold war era, but significantly underscoring the changes. This account posits that the opening up of the political space has allowed new actors such as parliament, business groups and the media to influence the conduct of Kenyan foreign policy. Ultimately Kenya’s domestic politics will remain critical to the continued pursuit of the country’s foreign policy goals and objectives